(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the analgesic effect and improvement in cervical spine range of motion of a combined therapeutic approach including electro-acupuncture, acupressure massage, and iontophoresis in the treatment of cervical scapulohumeralsyndrome to cervical spondylosis. Subjects and methods: This clinical interventional study comparing outcomes before and after treatment was conducted on 40 patients aged 38 years and above, diagnosed with cervical scapulohumeralsyndrome to cervical spondylosis. Patients received a combination therapy consisting of electro-acupuncture (20 minutes/session/day), acupressure massage (20 minutes/session/day), and iontophoresis using 5% sodium salicylate solution (15 minutes/session/day) for 15 consecutive days. Treatment efficacy was assessed using the Visual Analogue Scale (VAS) and the improvement in cervical spine range of motion. Results: After 15 days of treatment, the mean VAS score significantly decreased from 5.07 ± 0.69 to 2.18 ± 1.13 (p < 0.05). Cervical range of motion significantly improved post-treatment in all directions, including flexion, extension, left/right lateral flexion, and left/right rotation, compared to pre-treatment values (p < 0.05). Conclusion: The combination of electro-acupuncture, acupressure massage, and iontophoresis is an effective treatment option for reducing pain and enhancing cervical spine mobility in patients with cervical scapulohumeralsyndrome due to cervical spondylosis.